Conventional Hemodialysis is Associated with Greater Bone Loss than Nocturnal Hemodialysis: A Retrospective Observational Study of a Convenience Cohort. Issue 1 (1st June 2016) - Auguste, Bourne L.; Yuen, Darren; Chan, Christopher T.
Background: Compared with the general population, end-stage renal disease patients are at increased risk for bone loss and fractures. Nocturnal hemodialysis offers superior calcium-phosphate control and improved uremic clearance compared with conventional hemodialysis. Rates of bone loss by type of hemodialysis are unknown. Objectives: This study aims to determine whether there are differences in bone loss between frequent nocturnal hemodialysis and conventional hemodialysis. Design: This is a retrospective observational study. Setting: Participants were selected from two teaching hospitals in downtown Toronto. Participants: The study included 88 participants on dialysis for at least 6 months (52 patients on conventional hemodialysis and 36 patients converted from conventional hemodialysis to nocturnal hemodialysis). Patients on peritoneal dialysis and with previous renal transplants were excluded. Measurements: We obtained demographic variables and biochemical data by a chart review. We examined changes in bone mineral density at the hip (femoral neck, total hip) and spine (L1 to L4) measured at baseline and about 1 year in the two groups. Methods: We used Student's t test for evaluation of between-group mean differences in demographic and biochemical parameters. We used linear regression models adjusted for baseline age, weight, dialysis vintage, markers of mineral metabolism (serum phosphate, serum calcium, and parathyroid hormone), and baseline bone mineral density at the femoral neck, total hip, and lumbar spine to determine the annualized percent change by hemodialysis type. Results: Conventional hemodialysis subjects were older than nocturnal hemodialysis subjects (66 ± 9 vs 43 ± 10 years; p < 0.0001) with no significant differences in weight, dialysis vintage, serum phosphate, or parathyroid hormone between the two groups at baseline. In a period over 1 year, conventional hemodialysis compared to nocturnal hemodialysis subjects had significantly greater bone mineral density losses at all sites (1.6 % loss at the lumbar spine (95 % confidence interval (CI) 0.2–3.1), 1.3 % loss at the femoral neck (95 % CI 0.1–2.5), and 1.1 % loss at the total hip (95 % CI 0.1–2.6). Limitations: Some limitations to this study are the lack of medication administration history, short duration ( 1 year), and small sample sizes. Conclusions: This is the first study comparing bone density between hemodialysis modalities. Our study demonstrates that bone loss is less in nocturnal hemodialysis compared to that in conventional hemodialysis which may result in less fractures. Larger observational studies are ultimately needed to confirm preliminary findings from our study.